Circulating hemocytes of Mediterranean flour moth, Ephestia kuehniella Zell. (Lep: Pyralidae) and their response to thermal stress - V Ghasemi (Invertebrate Survival Journal, 2013)
The hemocytes of Ephestia kuehniella Zell. are arranged in five main classes: prohemocytes (PRs), plasmatocytes (PLs), granulocytes (GRs), oenocytoids (OEs) and spherulocytes (SPs). Two other morphotypes of hemocytes namely vermicytes (VEs) and podocytes (POs) were also distinguished in hemolymph of this species. Hemogram was studied in five developmental stages of the insect including early IVth, late IVth, early Vth and late Vth instar larvae as well as prepupa. Results indicated that total hemocyte count (THC) increased gradually with increasing in developmental stages and reached their maximal level in prepupa. Also, total cell numbers in the late IVth and Vth instar larvae and prepupa were significantly higher than that in the early IVth and Vth instar larvae. An increasing trend was found in hemolymph volume (HV) and number of hemocytes in circulation (HIC) with increasing in developmental stages of tested insect. PLs and GRs were the two abundant morphotypes of hemocytes in most stages. Mitotic index (MI) of hemocytes was found to be high in the early part of each stage than in the later larval stage and in prepupa. Heat and chill stresses were also assessed on hemocytes of 2-days old Vth instar larvae. The findings revealed that high temperature (40 °C) caused a significant increase in THC principally PLs, OEs and the MI along with a drastic reduction in number of GRs and HV. In contrast, chilling (4 °C) led to a significant reduction in THC, proportion of PLs and MI with increase in counts of OEs. Changes in the cytological features of the hemocytes of incubated larvae are also discussed